Use of Pearson and Spearman correlation testing in Indian anesthesia journals: An audit - Asha Tyagi; Rashmi Salhotra; Ananya Agrawal; Ishita Vashist; Rajeev K Malhotra (Journal of Anaesthesiology Clinical Pharmacology, 2023)
Background and Aims: Correct usage and interpretation of biostatistical tests is imperative. Aim of the present article was to evaluate the use of “correlation test” for biostatistical analysis in two leading Indian journals of anesthesia and sensitize the readers regarding its correct usage. Material and Methods: A prospective analysis was done for all original articles using the correlation test (Pearson or Spearman) that were published in “Indian Journal of Anaesthesia” (IJA) or “Journal of Anaesthesiology and Clinical Pharmacology” (JOACP) in the years 2019 and 2020. Results: Amongst all included original studies, correlation test were used in 6% (JOACP) and 6.5% (IJA) respectively (averaged for the years 2019 and 2020). Correlation test was usedinappropriately) for evaluating an aim of prediction/agreement/comparison, rather than association, in 25% and 10% instances each (JOACP and IJA). In both JOACP and IJA, there were high rates of using and interpreting results without citing 95% confidence intervals (CIs) of correlation coefficient (88% and 90%, respectively), P value for significance of the association (50% and 90%, respectively), or coefficient of discrimination (88% and 70%, respectively). In majority of the instances, test to ascertain presence of mandatory prerequisites such as normal distribution of data could not be found (62% and 90%, respectively). Conclusion: The complete potential of correlation test in exploring research questions is probably underappreciated. Further, even when used, its application and interpretation are prone to errors. We hope that the present analysis and narrative is a well-timed appropriate step in bridging the gaps in existing knowledge regarding use of correlation test in national anesthesia literature.